Pelatihan Pembuatan Tepung Pisang dan Produk Olahannya Bagi Ibu-Ibu Anggota PW Jemaat GKI Getsemani Kotaraja, Jayapura - Keiluhu, Henderina J.; Purnamasari, Vita; Wambrauw, Daniel Z.K.; Pallo, Aryanti S.; Alatubir, Rosalinda (Bakti Hayati: Jurnal Pengabdian Indonesia, 2024)
Banana is the well-known fruit plant with nearly every part of the plant can be used or consumed.  Banana fruit are rarely converted into banana flour, especially in Jayapura. Instead, they are typically eaten raw or processed into fried or chipped bananas. This community service project's objectives were to: (a) spread knowledge of the advantages of banana flour; and (b) teach people in making processed banana flour so that it can be sold for profit rather than just for personal use. After a lecture on banana flour benefit, participants were given the opportunity to make cakes using the flour. This project was conducted on August 26 and September 2, 2023 with 27 participants from the Gethsemane Indonesian Christian Church Women's Fellowship in the Kotaraja Jayapura area as participants. Banana flour was made using the drying method in the sun or in the oven. Cake products made from banana flour made in this activity were banana flour cookies and brownies. This activity received a good response and high satisfaction from activity participants, with the rate to 97%.